The impact of donor age and endothelial cell density on graft survival following penetrating keratoplasty. Issue 7 (13th November 2015) - Wakefield, M J; Armitage, W J; Jones, M N A; Kaye, S B; Larkin, D F P; Tole, D; Prydal, J
Abstract : Purpose: To determine if donor age and preoperative endothelial cell density (ECD) affect corneal endothelial failure following penetrating keratoplasty (PK). Methods: Preoperative and postoperative data for PKs performed in the UK between April 1999 and March 2012 were analysed. Donor age was split into three groups (0–60, 61–75 and >75 years) and donor ECD was split into three groups (≤2400, 2401–2600 and >2600 cells/mm 2 ). Cox proportional hazards regression was used to determine whether the selected subgroups of donor age and donor ECD have an impact on endothelial failure and a systematic analysis of the interaction between donor ECD and donor age was conducted. The analysis was stratified for primary corneal diagnosis (Fuchs endothelial dystrophy (FED), pseudophakic bullous keratopathy (PBK) and other) and corrected for potentially confounding factors (human leukocyte antigen matching, donor trephine diameter, deep vascularisation, the occurrence of reversible rejection episodes and receipt of systemic antiviral medication, long-term steroids or other immunosuppressive agents). Results: A total of 9415 patients, from the National Health Service Blood and Transplant UK Transplant Registry, who received their first PK for visual reasons were included in this study. The overall 5-year graft survival rate due to endothelial failure was 89%. Survival rates in recipients with FED, PBK and 'all other indications' were 95%, 83% and 89%, respectively. Our analysis shows that donor ECD did not affect outcome following corneal graft within the preselected categories, irrespective of diagnosis and after allowing for any potential confounding factors. Furthermore, HRs for each level of donor ECD, relative to >2600 cells/mm 2, for each combination of age group and indication, were not statistically significant. Conclusions: We were unable to detect a significant effect of donor age, up to 90 years, and preoperative donor ECD, above the lower limit of 2200 cells/mm 2, on endothelial failure at 5 years following PK.